2003
DOI: 10.1373/49.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Cell-free Plasma DNA Concentrations in Maternal Blood Are Stable 24 Hours after Collection: Analysis of First- and Third-Trimester Samples

Abstract: that Pyd and Dpd are poor markers of bone resorption in this clinical situation.Serum CrossLaps was highly correlated with ICTP at presentation and, to an even greater extent, after refeeding. By contrast, CrossLaps and ICTP showed no significant correlations with either (a) the urinary markers of bone resorption, Pyd and Dpd, or (b) markers of bone formation, even during catch-up weight gain when collagen synthesis, as reflected in PICP, was apparently supranormal. This suggests that CrossLaps and ICTP are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 15 publications
2
57
0
3
Order By: Relevance
“…A major factor to be considered is that as the blood samples were collected at a gestational age of 25 weeks, a greater amount of cffDNA was released into maternal blood. However, several studies have also shown that cffDNA is stable within the first 24 hours after sample collection (Angert et al, 2003;Zhang et al, 2008;Barrett et al, 2011). Based on the results of our study, it could be concluded that cffDNA was stable in blood samples for up to 2 days in both tubes.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A major factor to be considered is that as the blood samples were collected at a gestational age of 25 weeks, a greater amount of cffDNA was released into maternal blood. However, several studies have also shown that cffDNA is stable within the first 24 hours after sample collection (Angert et al, 2003;Zhang et al, 2008;Barrett et al, 2011). Based on the results of our study, it could be concluded that cffDNA was stable in blood samples for up to 2 days in both tubes.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, factors that influence the quantity of cffDNA have been investigated, including the time interval between the drawing of the blood and plasma processing (Angert et al, 2003;Xue et al, 2009), the type of collection tube used (Banfi et al, 2007), and the safe transport of specimens.…”
Section: Discussionmentioning
confidence: 99%
“…When the embryo are male the result of amplified were two bands, one 198 bp represent the DYS14 sequence, and other 97 bp represent the GAPDH sequence, while when embryo are female the results of PCR are one band at 97 bp represent GAPDH sequence. These results agreed with many investigators [14,[16][17][18].…”
Section: Discussionsupporting
confidence: 94%
“…Sample processing: within 6-8 h after collection (46)(47)(48) Use of specialized blood collecting tubes (Cell-Free RNA BCT 1 -Streck) that allow 7 days storage of blood by increasing cell stability and inhibiting nuclease mediated DNA degradation (48,49) 7-30% yearly DNA degradation during storage (50,51) cfDNA isolation:…”
Section: Kinetics Of Ddcfdna Levels In Recipients With Stable Graftsmentioning
confidence: 99%